Solusi Dosen dalam Menyelesaikan Kesulitan Penggunaan Metode Direct Method dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing di PTKIN - Giyoto Giyoto (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
This research aims to describe the solutions of lecturers’ difficulties in the use of Direct Method in learning Indonesian language for foreign speakers (BIPA). Data sources in the form of open ended questionnaires distributed to BIPA teaching lecturers at PTKIN, especially at UIN Raden Mas Said Surakarta UIN Syarif Hidayatullah Jakarta. Descriptive research methods are used in analizing the data of ten of ten prime principles of Direct Method focusing on the solutions of theis difficulties into three aspects: lingual, personal, technical/media, and cultural aspects. The results of the study are difficulty in the form of students having difficulty mastering the system of indonesian phonemes, cultural concepts and abstract meanings that are not yet known in their country, different student motivations, students are reluctant to use Indonesian in the need for interaction, students learn two or more languages. Solutions taken by lecturers are: dictating the shape of the sound and practicing the spelling of indoensia phonemes; practicing using BIPA books; using videos, images, gestures, and other media through the internet; ask to mingle in the language community, learn with peers, and individual guidance.